Gas–thermal–solid coupling analysis of a hypersonic inflatable reentry and descent system - Cao, Xu; Xu, Rui; Yu, Li; Zhao, Xiaoshun; Wang, Qi (Frontiers in Materials, 2023)
Hypersonic reentry has a severe flight environment during spacecraft return. To analyze the influence of pneumatic loads on the flexible structure under the extreme load condition during the deceleration process of inflatable reentry and descent system, fluid–and thermal–solid couplings have been studied. In addition, the stress and structural deformation distributions and the temperature distribution of each functional layer of the flexible thermal protection system were obtained in this study. The influence of flight conditions and structural parameter changes on inflatable structure performance was studied, and the transient response mechanism of the pneumatic load to the inflatable structure was revealed. The results showed that the mechanical–thermal–structural coupling analysis method could predict the mechanical properties of flexible inflatable deceleration structures, which can provide references for the aerodynamic configuration and thermal protection design under extreme flight conditions.